Indigenism, Pan-Indigenism and Cosmovisionism The Confluence of Indigenous Thought in the Americas - Mantilla, Martha E. (Seminar on the Acquisition of Latin American Library Materials, 2015)
Selected papers from the annual conference of the Seminar on the Acquisition of Latin American Library Materials